Budi daya Terapung Tanaman Sawi Hijau dengan Perbedaan Dosis Pupuk NPK, Ukuran Polibag, dan Waktu Pemupukan - Erna Siaga; Benyamin Lakitan (Institut Pertanian Bogor, 2021)
Cultivation of mustards green on floating raft is one of alternative cultivations which is applied by traditional farmers during flooding period in Riparian Wetland. The cultivation will increase Cropping Index and farmer’s income. The objective of this research is to evaluate growth and yield of mustards green on floating cultivation with the application of different NPK doses, polybag sizes, and fertilization times to find cultivation of mustards green which effective and efficient. This research was conducted on October 2016–February 2017 in Jakabaring Facility (104°46’44” E; 3°01’35” S) and Kimia Hasil Pertanian (LKHP) Laboratory, Fakultas Pertanian, Universitas Sriwijaya, Palembang. This research consisted of two steps. The first experiment used a completely randomized design with four doses of NPK (16:16:16) namely 0 (control), 5, 10, and 15 g plant-1. The second experiment used a Split Plot Design consisted of two factors namely polybag size (A1 and A2) and fertilization time (F1, F2, and F3). The result of the first experiment showed that utilization three doses of NPK significantly increased shoot length, number of leaves, and fresh weight compared control. The second experiment showed that polybag size and fertilization time did not significantly affect growth and yield parameters. Utilization of 5 g plant-1 of NPK on 1 week after transplanting (WAT) which used polybag size of 30 x 30 cm on growing media consisted of soil, manure, and rice husk (1:1:1/v:v:v) produced an effective and efficient cultivation of mustards green. Keywords: fertilizing, floating cultivation, green mustard, NPK